Improved plasticity of Inconel 718 superalloy fabricated by selective laser melting through a novel heat treatment process. (15th October 2019) - Li, X.; Shi, J.J.; Cao, G.H.; Russell, A.M.; Zhou, Z.J.; Li, C.P.; Chen, G.F.
Abstract: When Inconel 718 alloy is fabricated by selective laser melting and treated by traditional homogenization plus double aging heat treatment (HA), its strength improves greatly, but ductility decreases. A novel heat treatment (NHT) including higher temperature homogenization at 1150 °C for 2 h and one-time lower temperature aging treatment at 700 °C for 12 h is developed, which can overcome the strength-plasticity trade-off of Inconel 718 alloy. The results show that recrystallized grains with annealing twins and ultrafine strengthening phases form in the specimen subjected to the NHT. These microstructures differ from those in as-built and conventional heat-treated samples. Especially the morphology of strengthening phase γ″-Ni3 Nb precipitated in the NHT specimen has changed a lot, it seems to be spherical rather than disc-like shape occurred in the traditional heat-treated samples. Consequently, the NHT process increases plasticity by 41%, while maintaining ultimate strength at the same level achieved by the traditional heat treatment. The enhanced ductility is attributed to the annealing twins and recrystallized grains without local strains, while the strength is provided by the smaller precipitates formed in the NHT one-time aging treatment. Graphical abstract: Unlabelled Image Highlights: A novel heat treatment process was proposed for Inconel 718 superalloy. The morphology of γ″ phase was modified by one-time aging heat treatment. The recrystallized grains with annealing twins promoted good plasticity.